Prospective Teachers’ Reasons: The Importance of Reading a Book - Birsen Doğan (Bilgi Dünyası, 2014)
Prospective teachers play an important role in establishing the literacy proficiency of future generations. However, this situation also suggests such points as types of prospective teachers’ attitudes towards reading and the reason of their reading. In order to investigate these points, this study was designed descriptively. An open-ended questionnaire was used to collect the data through 132 prospective teachers from Instructor Training Program of Education Faculty at Pamukkale University. The data was analyzed based on the rules of content analysis. The results about prospective teachers’ views on the importance of reading were categorized into three themes as academic, social and personal reasons and each theme was presented by frequencies and percentages of participants’ responses. The findings of this descriptive study indicated that prospective teachers viewed reading as important for academic, social and personal reasons. The academic theme is divided into three sub-themes as acquiring the knowledge, improving language skills and developing critical and creative thinking skills. The social theme is comprised of five sub-themes as appreciating alternative perspectives, participating in society, recognizing and understanding different peoples and cultures, learning about current events, establishing empathy. Finally, the personal theme is divided into five sub-themes as developing personal identity, organizing one’s life, relaxation, experiencing enjoyment, happiness.